Analysis of Musical Drama “Udin and the Magic Book” - Kuswaty, M; Cahyani, I (KnE Social Sciences, 2019)
Primary school students are generally happy if given the opportunity to perform on the stage. The role of teachers is crucial in building the students’ positive characters and competencies in the 21st century, to be ready to show their interests and talents. Therefore, the researchers will analyze the musical drama performance by primary school students of Mutiara Bunda Bandung. This study aims to analyze the Sundanese musical drama performance entitled “Udin and The Magic Book”. This study used descriptive qualitative method which the results of the data analysis shows that the content of the musical drama “Udin and The Magic Book” aims to invite the students to know the traditional Sundanese songs and games, persuade them to help their parents, encourage the students to diligently read books, teach them about the 21st century competence which is to love the nation and country, to have a global perspective, and be proud of their local culture. Based on the performance of the students during the show, the students looked confident, were capable of improvisation, and could control the stage area. The significance of this show is that the children were trained early to develop their 21st-century competence through artistic performances. Keywords: musical drama, performing arts, 21st century